Introduction to the theory of Cultural Anthropology: It is a theotitical- Analytical study - Jabar Qader Ahmed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
Cultural anthropology is a branch of anthropology is one of the new sciences that studies different societies, their cultures, political, social, religious, and economic systems. This science provides accurate and realistic explanations for events. Anthropologists focus on various aspects such as cultural distinction, social institutions, racial cultures, lifestyle relationships, and social interactions between developing and developed societies. Cultural anthropology studies the cultures of various societies. It presents a detailed and intense presentation of the major types of culture. Even though, technology and the opening of borders consolidate one culture over others, or increase its influence, because cultural differences become more noticeable due to the breadth and influence of technology. Some of the time, technology, material changes, and innovations in one culture directly influence the culture and social structures of another society. In a few cases, the impact of material culture on society is solid. Moreover, Intercultural mixing and cultural interaction in societies take place through distinct processes. This study is a theoretical-analytical investigation of cultural anthropology that goes into deeper detail to clarify the theoretical underpinnings and methodological facets of the field. The study's findings demonstrate the value of cultural anthropology in understanding various cultures and analyzing how societies are changing on a cultural and social level. They also demonstrate the significant impact of culture on social group interactions, relationships, and behavior.